Efficacy of electroacupuncture on insomnia disorder in older adults: study protocol for a multicentre randomised controlled trial - Mao, Jinfeng; Liu, Huirong; Wang, Zhaoqin; Zhang, Ming; Xu, Shifen; Chen, Jianhua; Ye, Wujie; Yang, Yuechang; Li, Jing; Li, Jianping; Tao, Yingna; Wu, Luyi; et al. (Frontiers in Neurology, 2025)
IntroductionInsomnia disorder is highly prevalent among older adults and is associated with significant adverse effects on both physical and psychological health. The use of hypnotic medications in this population is often accompanied by undesirable risks, including drug tolerance, dependence, and impaired daytime functioning. While electroacupuncture has been increasingly employed as a therapeutic modality for insomnia, robust clinical evidence supporting its efficacy and safety remains limited. This multicentre randomised controlled trial is designed to evaluate the therapeutic effectiveness and safety profile of electroacupuncture in the treatment of insomnia disorder in older adults.Methods and analysisThis multi-centre, single-blind, randomised controlled trial will enrol 214 older adults with diagnosed insomnia disorder from five hospitals. Participants will be randomly assigned in a 1:1 ratio to receive either electroacupuncture or sham electroacupuncture. The electroacupuncture group will undergo treatment three times per week for 8 weeks. The sham electroacupuncture group will receive a non-penetrative placebo needle intervention at sham acupoints, with no electrical stimulation delivered despite connection to the electroacupuncture apparatus. The primary outcome will be the change in Pittsburgh Sleep Quality Index score. Secondary outcomes will include the Insomnia Severity Index, actigraphy-derived sleep parameters, sleep diaries, the Hospital Anxiety and Depression Scale, and the Mini-Mental State Examination. All outcomes will be assessed at baseline (week 0), during intervention (weeks 4 and 8), and during follow-up (weeks 12 and 20).DiscussionIf the intervention demonstrates efficacy, this study will provide important clinical evidence supporting electroacupuncture as a safe and effective non-pharmacological treatment for insomnia in older adults. The findings may influence clinical practice by expanding therapeutic options and improving sleep quality in this vulnerable population.Clinical trial registrationhttp://www.chictr.org.cn, identifier ChiCTR2400081782.